Damage to Banana Plants By Leaf Roller Caterpillar (Erionota thrax L) On Ambon Island - Wulandari Subari; Nureny Goo; Victor George Siahaya (Agrologia, 2022)
ABSTRACTThe study aimed to obtain data on the attack intensity of Erinota thrax at different altitudes of places and find out the banana  cultivars with the lowest attack intensity.  This study used a random sampling method at three locations with different heights. The data analysis used is  a simple quantitative analysis to determine the magnitude of the attack  intensity.   The intensity of E. thrax attacks in three different places has varying percentages.  The number of leaf rolls Tulehu Village is 300 with a damage intensity  of 63.14% (heavy),   Keranjang Village was 200 with a damage intensity of 59.36% (heavy), and Tawiri Village was 187 with a damage intensity of 39.11% (medium). The greatest number of leaf rolls is 14 per leaf blade.  The lowest intensity in Tawiri Village is dominated by the cultivars of Kepok  and Emas, while the highest intensity is in Tulehu Village and Keranjang Village which is dominated by three cultivars, Raja, Kepok, and Emas. The difference in numbers between leaf rolls and larval populations is thought to be due to environmental parameters, such as wind and precipitation.